2017
DOI: 10.1177/1352458517731912
|View full text |Cite
|
Sign up to set email alerts
|

Medication usage and falls in people with multiple sclerosis

Abstract: There is a need to identify modifiable risk factors for falls in people with multiple sclerosis (MS) to enable the design of successful falls prevention interventions. There is conflicting evidence regarding the association between medication use and occurrence of falls in MS. A total of 101 people with MS had medications classified using the Anatomical Therapeutic Classification system and number of falls prospectively monitored for 3 months. No association was noted between number of medications and falls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…18 Indeed, pwMS are particularly prone to falls and have an elevated risk of potentially life-threatening infections, possibly due to physical disability as well as immunosuppressive treatments. 7,34 In other words, ageing pwMS are at higher risk to be frail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Indeed, pwMS are particularly prone to falls and have an elevated risk of potentially life-threatening infections, possibly due to physical disability as well as immunosuppressive treatments. 7,34 In other words, ageing pwMS are at higher risk to be frail.…”
Section: Discussionmentioning
confidence: 99%
“…24 Despite recent progress characterized by the advent of new disease-modifying therapies resulting in a better, although partial, control of the early inflammatory phase of the disease, pwMS still show an increased risk of accidents and falls, a higher utilization of acute and chronic healthcare facilities and, ultimately, a younger age at death compared to the general population. 59…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the literature in elderly populations, medications, in terms of quantity and class, are associated with higher falls rates in most studies published on this topic. 51,52 During the last decade a wide variety of disease modifying drugs (DMD's) have been introduced in MS. The challenge is to examine whether immunomodulatory drugs differ when examining falls in the MS community.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…The challenge is to examine whether immunomodulatory drugs differ when examining falls in the MS community. This issue was partly addressed by Comber et al 52 who investigated the effect of medication usage on falls in MS. They reported that participants taking medications categorised as genitourinary and sex hormones or centrally acting muscle relaxant medications had increased odds of being a faller.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Furthermore, some drugs that are broadly used in neurologic setting may even worsen gait and balance of patients with MS, including antidepressants (selective serotonin reuptake inhibitor and serotonin and norepinephrine reuptake inhibitor), centrally acting muscle relaxants, genitourinary medications and sex hormones ( Table 3 ). 73 , 74 If there is also a dose-dependent effect of the aforementioned classes of medications on the risk of accidental falls is still controversial. 22 , 75 , 76 …”
Section: Introductionmentioning
confidence: 99%